Acute Liver Failure - Lee, William M. (Seminars in Respiratory and Critical Care Medicine, 2012)
Acute liver failure (ALF) (sometimes referred to as fulminant hepatic failure) is a clinical syndrome from a variety of causes resulting from rapid loss in hepatocyte function, typically associated with coagulopathy and encephalopathy in a patient without preexisting liver disease or cirrhosis. Cerebral edema is a cardinal feature and may produce uncal herniation, yielding brain stem compression and death. The typical interval from onset of symptoms to onset of encephalopathy is 1 to 2 weeks, but cases evolving more slowly, up to 6 months, may still be included in the definition. ALF is rare, affecting 2000 patients annually in the United States, and comprises ∼7% of liver transplants annually. Currently, in the United States, acetaminophen accounts for ∼50% of all cases of ALF, but other etiologies include hepatitis, drug-induced liver injury, autoimmune hepatitis. Prior to the availability of liver transplantation (LT), mortality of ALF was extremely high, often exceeding 90%; most common causes of death were multiorgan failure, hemorrhage, infection, and cerebral edema. Fortunately, survival has improved considerably in the last 3 decades (overall survival now exceeds 60%). In large part, this improved survival reflects the option of LT but also reflects the high frequency of acetaminophen toxicity as a cause of ALF. In fact, most patients with ALF are not candidates for LT. Critical care of patients with ALF is key to their survival, and decisions must sometimes be made with inadequate information. We review standard practices (medical, pharmacological, and LT) and new research initiatives and findings for this interesting but vexing orphan disease. Particular attention will be paid to practical matters for clinicians to consider in approaching the ALF patient.
Keywords: acute liver injury; acetaminophen toxicity; coagulopathy; encephalopathy; hepatic necrosis